The Analysis of Integration of Ideological Political Education With Innovation Entrepreneurship Education for College Students - Zhao, Xinyuan; Zhang, Jinle (Frontiers in Psychology, 2021)
This study is to analyse the integrated construction and application of ideological and political education (IPE) and innovation and entrepreneurship education (IEE) in colleges based on the positive psychological quality of entrepreneurship. 549 college students are selected for a questionnaire survey. The correlations between entrepreneurial psychological quality of college students, IEE in colleges, IPE, and entrepreneurial self-efficacy are analysed with the Spearman correlation and linear regression. The hierarchical regression analysis is used to analyse the intermediary role of entrepreneurial self-efficacy in IEE, IPE in colleges, and entrepreneurial psychological quality of college students. The results show that the entrepreneurial psychological quality of college students is significantly different in gender, family location, and grade level (p < 0.05); the main channels of IPE and daily IPE have significant positive effects on the positive entrepreneurship psychological quality (p < 0.05), and have extremely significant positive effects on the entrepreneurial self-efficacy (p < 0.001); innovation and entrepreneurship course, innovation and entrepreneurship practices, innovation and entrepreneurship environment, and total score of IEE have significant positive correlations with positive entrepreneurship psychological quality and entrepreneurial self-efficacy of college students (p < 0.05); the intermediary effect of entrepreneurial self-efficacy accounts for 33.49% on the IPE and entrepreneurial psychological quality, and 41.85% on IEE and entrepreneurial psychological quality. In short, IPE and IEE can effectively improve the positive psychological quality and self-efficacy of college students, and the joint construction of the two can have a more significant effect.